DENSITY FUNCTIONAL THEORY, RESTRICTED HARTREE- FOCK SIMULATIONS AND FTIR, FT-RAMAN STUDIES ON GABAPENTIN - T.RAMYA; S.GUNASEKARAN; G.R.RAMKUMAAR (International Journal of Pharma and Bio Sciences, 2015)
Gabapentin purposefully synthesized to mimic the chemical structures of the neurotransmitter γ-aminobutyric acid and for use as an adjunctive medication to control partial seizures. In this work, the vibrational spectral analysis was carried out on Gabapentin by using FT-Raman and FTIR spectroscopy in the range 5000 - 50 cm -1 and 4000 - 450 cm -1respectively. Quantum chemical calculations of geometrical structure, vibrational wavenumber and infra red intensities were carried out by the ab inito Restricted Hartree Fock (RHF) and Density Functional Theory DFT (B3LYP) with complete relaxation in the potential energy surface using 6-311++G(d,p) basis set. The complete vibrational assignments of wave numbers were made on the basis of potential energy distribution (PED).The results of the calculations were applied to simulated spectra which shows good agreement with the observed spectra. Natural Population analysis (NPA), HOMO and LUMO energy, electric dipole moment(μ), hyperpolarizability(β), chemical reactivity, 1H NMR and 13 C NMR and thermodynamic properties are also calculated using RHF and DFT methods.